Pengaruh Suhu dan Waktu Penyeduhan Dalam Variasi Jenis Teh Terhadap Kadar Flavonoid Total Menggunakan Spektrofotometri UV-Vis - Taufiq, Mawaddah; Yuniarto , Prayoga F.; Sukmawati , Datin An Nisa; Kadir , Mujtahid bin Abd (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2025)
Tea derived from the tea plant (Camellia sinensis) is a plant that consists of many types and is spread in various countries. In tea leaves, the flavonoid content varies. This is caused by several factors: tea plant variety, leaf age, leaf picking method, planting location, temperature, and processing. Based on the habits of people in Indonesia who brew tea with hot water at a temperature of 700C or 1000C in this study, the flavonoid content in each type of tea was extracted using several variations in temperature and brewing time which aims to determine the maximum level of flavonoid content in tea variations. Determination of flavonoid levels in tea that has been extracted will be determined using uv-vis spectrophotometry. The results of this study show that the initial temperature and brewing time affect the total flavonoid content of various types of tea. Flavonoid levels in green tea, oolong tea, black tea, and pu-erh tea have the highest levels at a temperature of 1000C within 10 minutes with green tea levels at 9,80 mg/g, oolong tea 7,02 mg/g, black tea 4,22 mg/g and pu-erh tea 2,61 mg/g. While white tea has the highest level at 1000C in 5 minutes with the highest level of white tea at 3,76 mg/g.